Floristic Diversity of Grasses (Poaceae) in Selected Wetlands of Tirunelveli District, Tamil Nadu - Subramani Vijay Sharma; Murugan Manisha; Perumal Ravichandran (The Bioscan, 2026)
The present study evaluates the diversity and distribution of grasses (Poaceae) in selected wetland habitats of Tirunelveli district, Tamil Nadu, South India. Field surveys were conducted from July 2022 to March 2023 across marshes, paddy fields, pond margins, and riverine ecosystems. A total of 88 grass taxa belonging to 48 genera and six subfamilies were recorded, including five taxa endemic to Tamil Nadu. Among the subfamilies, Panicoideae was the most dominant in diversity with 53 species, followed by Chloridoideae (28), while Aristidoideae (3), Micrairoideae (2), Arundinoideae (1), and Oryzoideae (1) were lesser represented. The results emphasize the floristic richness and conservation significance of wetlands in the Tirunelveli district and provide baseline information for wetland biodiversity management and conservation planning.